Islamic Educational Values in the Implementation of the Ngarosul Tradition among the Community of Margabakti Village, Cibeureum District, Tasikmalaya - Yunanda, Resta; Aropah, Imas; Iqbal, Mohammad Iqbal; Hamdani, Djaswidi Al; Rizal, Soni Samsu (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
Etymologically the ngarosul ritual is a local tradition that centers on appointing an individual deemed religiously competent to lead prayers for a person who is approaching death. The core of this tradition lies in the community’s spiritual supplication: if the person being prayed for is still granted the opportunity to live, it is hoped that they will be swiftly restored to health; however, if their time has come, it is expected that their passing will occur peacefully and without obstacles. This study aims to provide an in-depth description of the Islamic educational values embedded within the practice of the ngarosul tradition in Cibeureum, Tasikmalaya. The researcher employed a qualitative approach through field research to examine this phenomenon empirically. Data were collected comprehensively through observation and in-depth interviews with informants, as well as direct engagement with the research setting and the ritual activities taking place. Based on the analysis, the study found that the ngarosul practice embodies strong religious and educational values that significantly influence the spiritual life of the local community. This tradition not only functions as a ritual expression but also serves as a medium for internalizing Islamic teachings, particularly those relating to tawakkul (trust in God), sincere effort, respect for the processes of life and death, and the reinforcement of social solidarity within the community